PENGARUH PERMAINAN CREPE PAPER LASER MAZE TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI RA MAU’IZAH HASANAH KECAMATAN TAMPAN KOTA PEKANBARU - Novriana, Ira Aufa; Novianti, Ria; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the results of field observation on the gross motor abilities of children has not developed optimally. So it is necessary to implement the activities that spur the abusive motor abilities of children. This study aims to determine the effect of crepe paper laser maze activity on gross motor skills of children aged 5-6 years in RA Mau'izah Hasanah Tampan Sub District Pekanbaru City. The sample used in this study was 30 children. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS vers. 20. The research hypothesis is the game crepe paper laser maze has an effect on gross motor skills aged 5-6 years in RA Mau'izah Hasanah Tampan Sub-district Pekanbaru City. This can be known from the analysis of data obtained t-count = 3.979 and Sig. (2-tailed) = 0.000. because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a significant difference in motor abilities of children after performing the game of crepe paper laser maze. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after do the game crepe paper laser maze. The influence of the game of crepe paper laser maze on gross motor skills of children aged 5-6 years in RA Mau'izah Hasanah Tampan District Pekanbaru City is 69.13%.Keywords: Gross Motor Ability, Crepe Paper Laser Maze Games